Forensic odontology : principles and practice - Taylor, Jane A.; Kieser, Jules (Chichester, West Sussex, UK ; Hoboken, NJ : John Wiley & Sons Inc., 2016)
Forensic odontology refers to the science and practice of dentistry which may be applied to help solve litigation in both criminal and civil cases. It is a specialist branch of dentistry that assists the legal system in the handling, analysis and interpretation of dental evidence. --
Forensic Odontology: Principles and Practice pulls together the very latest research findings and advice on best practice and essential skills, including aspects of forensic science that provide a well-rounded educational experience for the reader. Chapters provide coverage of anatomy and morphology, mortuary techniques, physical anthropology, applied forensic sciences, child and elder abuse, and facial approximation. The text introduces the various topics and discusses underpinning philosophies without being an exhaustive historical treatise. Appropriate case studies are used to highlight issues, and references to current research are provided to stimulate further reading and research. --
Foundation knowledge in forensic odontology -- Jurisprudence and forensic practice -- Anatomy and morphology -- Forensic pathology -- Human identification -- Mortuary techniques -- Age assessment -- Bite marks -- Forensic odontology in disaster victim identification -- Forensic anthropology -- Introduction -- Odontology opinions -- Forensic odontology management -- Application of post-mortem computed tomography to forensic odontology.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Dental jurisprudence; MEDICAL -- Forensic Medicine; MEDICAL -- Preventive Medicine; MEDICAL -- Public Health; Dental jurisprudence; Forensic Dentistry; Electronic books; Electronic books